2012
DOI: 10.1016/j.krcp.2012.04.536
|View full text |Cite
|
Sign up to set email alerts
|

examination of the effects of liraglutide on diabetic nephropathy

Abstract: Body Cell Mass (BCM) is a sum of all metabolically active cells of the body. Aim of the study was to compare BCM with other nutritional and inflammatory markers in patients with chronic kidney disease (CKD) stage 4-5 (NKF) without dialysis treatment and in hemodialysis patients(HD). We included 45 adult patients with CKD and eGFR o30 ml/min not treated with dialysis (26 male, age: 59,7 7 16,8) and 39 adults treated with HD three times a week, for more than three months (26 male, 5 diabetics, age: 59,8 716). Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Despite a significant improvement in HbA 1c from baseline (by −0.8% [−8.7 mmol/mol]) at the end of the study, sitagliptin was associated with an increase in UACR from baseline by +18 and +6% after 24 and 54 weeks of treatment, respectively ( 23 ). In another study using an injectable GLP-1 analog, Ryuge et al ( 24 ) found that liraglutide was not associated with any changes in renal function or albuminuria after 24 weeks of treatment in patients with diabetic nephropathy. However, these data must be interpreted with caution because both studies provide observational assessments of renal parameters and were not designed specifically to assess changes in albuminuria ( 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite a significant improvement in HbA 1c from baseline (by −0.8% [−8.7 mmol/mol]) at the end of the study, sitagliptin was associated with an increase in UACR from baseline by +18 and +6% after 24 and 54 weeks of treatment, respectively ( 23 ). In another study using an injectable GLP-1 analog, Ryuge et al ( 24 ) found that liraglutide was not associated with any changes in renal function or albuminuria after 24 weeks of treatment in patients with diabetic nephropathy. However, these data must be interpreted with caution because both studies provide observational assessments of renal parameters and were not designed specifically to assess changes in albuminuria ( 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…In another study using an injectable GLP-1 analog, Ryuge et al ( 24 ) found that liraglutide was not associated with any changes in renal function or albuminuria after 24 weeks of treatment in patients with diabetic nephropathy. However, these data must be interpreted with caution because both studies provide observational assessments of renal parameters and were not designed specifically to assess changes in albuminuria ( 23 , 24 ). Prospective, randomized, controlled clinical trials are now needed to assess the renal effects of incretin-based therapies in patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After 6 months of liraglutide administration, the blood glucose levels and average HbA1c were significantly reduced, though, no significant changes in kidney function. The outcomes suggested the improvement in glucose metabolism and body mass index reduction without observable changes in kidney function after administration of liraglutide to diabetic nephropathic patients (Ryuge et al 2012). In support of this study, it has been planned to study the effect of liraglutide on proteinuria and the progression of diabetic nephropathy in T2DM patients.…”
Section: Diabetic Nephropathymentioning
confidence: 91%
“…Liraglutide was not associated with any changes in renal function after 24 weeks in patients with DN (eGFR <60 mL/min). 70 Sitagliptin, saxagliptin and linagliptin may have the potential for beneficial renal effects. Sitagliptin (50 mg/day) reduced urinary albumin-to-creatinine ratio (UACR: −20.6 mg/g creatinine) after 24 weeks in patients with T2DM; the effect was observed in patients with normo-, micro- and macroalbuminuria.…”
Section: Glp-1 Analogues and Dpp-4 Inhibitorsmentioning
confidence: 99%